2005
DOI: 10.1038/sj.embor.7400379
|View full text |Cite
|
Sign up to set email alerts
|

Methylation: lost in hydroxylation?

Abstract: Methylation of histone tails is a key determinant in forming active and silent states of chromatin. Histone methylation was regarded as irreversible until the recent identification of a lysinespecific histone demethylase (LSD1), which acts specifically on mono-and dimethylated histone H3 lysine 4. Here, we propose that the fission yeast protein Epe1 is a putative histone demethylase that could act by oxidative demethylation. Epe1 modulates the stability of silent chromatin and contains a JmjC domain. The Epe1 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
150
0
2

Year Published

2006
2006
2018
2018

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 188 publications
(154 citation statements)
references
References 37 publications
2
150
0
2
Order By: Relevance
“…Recent structure analysis of jmjC of HIF1AN/FIH, which has a 2-oxoglutarate (2-OG)-Fe(II)-dependent dioxygenase activity, revealed residues binding to the cofactors 2-OG and Fe(II), and showed that the domain contains a doublestranded ␤-helix motif (Elkins et al, 2003). A sequence alignment of the jmjC domains of various jumonji family proteins suggested that these features are conserved (Elkins et al, 2003;Trewick et al, 2005). Recently, one jumonji family protein, FBXL11/ JHDM1A was shown to be a 2-OGFe(II)-dependent histone demethylase .…”
Section: Structure and Evolution Of Jumonji Family Proteinsmentioning
confidence: 99%
See 4 more Smart Citations
“…Recent structure analysis of jmjC of HIF1AN/FIH, which has a 2-oxoglutarate (2-OG)-Fe(II)-dependent dioxygenase activity, revealed residues binding to the cofactors 2-OG and Fe(II), and showed that the domain contains a doublestranded ␤-helix motif (Elkins et al, 2003). A sequence alignment of the jmjC domains of various jumonji family proteins suggested that these features are conserved (Elkins et al, 2003;Trewick et al, 2005). Recently, one jumonji family protein, FBXL11/ JHDM1A was shown to be a 2-OGFe(II)-dependent histone demethylase .…”
Section: Structure and Evolution Of Jumonji Family Proteinsmentioning
confidence: 99%
“…Recently, one jumonji family protein, FBXL11/ JHDM1A was shown to be a 2-OGFe(II)-dependent histone demethylase . The alignment of sequences for the dendrogram was made by taking previously predicted conservative residues such as cofactor binding sites (Clissold et al, 2001;Trewick et al, 2005; SMART and Pfam databases; Fig. 2).…”
Section: Structure and Evolution Of Jumonji Family Proteinsmentioning
confidence: 99%
See 3 more Smart Citations